Levels of Internal Indole-3-acetic Acid and Abscisic Acid in Different Physiological Growth Periods in The Leaves of Loquat (Eriobotrya japonica Lindl.) Fruit - ERSOY, NILDA; KAYNAK, LAMI (Asian Journal of Chemistry, 2010)
The loquat fruit variety, which blooms in fall and bears flowers and fruit in winter, differs from other varieties in terms of periods of physiological growth. Plants produce the nutrients they need with their leaves. Hence, it is important to determine the levels of internal growth regulating substances found in leaves of the loquat fruit in different growth periods. The present study aims to determine internal indole-3-acetic acid (IAA) and abscisic acid (ABA) levels by taking samples from the leaves of the Gold Nugget and Akko XIII loquat fruit varieties in different physiological growth periods. According to the results, the total-IAA level increased two-fold in the first year in May, when fruit begin to ripen, in comparison to August, when morphological differentiation occur, an one-fold in the second year. The total-IAA level in the Akko XIII loquat fruit variety increased one-fold in May in comparison to August in the first year and 4-fold in the second year. The total-ABA level in the Gold Nugget loquat fruit variety decreased three-fold in May in comparison to August in the first year and four and a half-fold in the second year. On the other hand, the total-ABA level in the Ako XIII loquat fruit variety decreased nearly three-fold in May, when fruit begin to ripen, in comparison to August, when morphological differentiation occurred and 3-fold in the second year.